Application of enhanced recovery after surgery for oral dryness prevention after endoscopic sinus surgery - Yanhong Wei; Fanglian Shu; Ying Dai; Aji Tan; Yanju Wang; Li Zhang; Yan Shu (Brazilian Journal of Otorhinolaryngology, 2024)
Objective: To investigate the efficacy of cluster nursing intervention based on Enhanced Recovery After Surgery (ERAS) for xerostomia in chronic rhinosinusitis after nasal endoscopic surgery. Methods: A total of 80 patients with chronic rhinosinusitis who underwent functional nasal endoscopic surgery between January 2020 and December 2021 were selected and randomly divided into a control group (n = 40) and an experimental group (n = 40). Patients in the control group were treated with general nursing, while ERAS-based cluster nursing intervention was adopted for the experimental group, in addition to general nursing. Xerostomia stage and comfort level were observed at 2 h, 6 h, 24 h and 48 h after surgery; negative emotions before and after nursing were also observed. Results: After the intervention, the xerostomia stage and comfort level at 6, 24 and 48 after surgery were higher in the experimental group (p < 0.05). Negative emotions in the experimental group were lower after nursing (p < 0.001). The self-rating depression scale and self-rating anxiety scale scores increased after nursing in both two groups (p < 0.05). Conclusion: Enhanced recovery after surgery-based cluster nursing intervention can alleviate xerostomia, improve patients' comfort levels, reduce their negative emotions and accelerate postoperative recovery. Level of evidence: 2.